1998
DOI: 10.1021/bi981193u
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Isoprenyl Tail of Ubiquinone in Reaction with Respiratory Enzymes:  Studies with Bovine Heart Mitochondrial Complex I and Escherichia coli bo-Type Ubiquinol Oxidase

Abstract: The hydrophobic isoprene tail of ubiquinone-2 (Q2) exihibits binding specificity in redox reactions with bovine heart mitochondrial complex I (Ohshima, M., Miyoshi, H., Sakamoto, K., Takegami, K., Iwata, J., Kuwabara, K., Iwamura, H., and Yagi, T. (1998) Biochemistry 37, 6436-6445) and the Escherichia coli bo-type ubiquinol oxidase (Sakamoto, K., Miyoshi, H., Takegami, K., Mogi, T., Anraku, Y., and Iwamura, H. (1996) J. Biol. Chem. 271, 29897-29902). To identify the structural factor(s) of the diprenyl tail of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…It is possible that the binding of IDE is enhanced by hydrogen bonding between its terminal hydroxyl group and a nearby charged residue in the site. For the hydrophobic site, Sakamoto and co-workers studied the reduction of a range of coenzyme Q 2 derivatives by complex I (53). They concluded that the role of the tail is not simply to enhance the hydrophobicity and attributed the high affinity of Q 2 itself to molecular interactions between the binding site and the methyl branch and π-system of the first isoprene unit.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the binding of IDE is enhanced by hydrogen bonding between its terminal hydroxyl group and a nearby charged residue in the site. For the hydrophobic site, Sakamoto and co-workers studied the reduction of a range of coenzyme Q 2 derivatives by complex I (53). They concluded that the role of the tail is not simply to enhance the hydrophobicity and attributed the high affinity of Q 2 itself to molecular interactions between the binding site and the methyl branch and π-system of the first isoprene unit.…”
Section: Discussionmentioning
confidence: 99%
“…Low efficiencies per se do not necessarily dispute the occurrence of catalytic reduction at the quinone reaction site because (i) the apparent electron transfer efficiency of hydrophobic UQ 4 is also low in SMPs, and (ii) the efficiencies of UQ 2 and decyl-UQ (an alkyl derivative of UQ 2 ) markedly vary even with slight structural modifications in the side chain as well as the quinone head-ring (42,43). Therefore, the result that their head-rings reached the reaction site is difficult to reconcile with the channel models.…”
Section: Quinone/inhibitor-binding Pocket In Respiratory Complex Imentioning
confidence: 99%
“…The effects of various inhibitors on the steady state kinetics of the enzyme have provided further evidence that there must be more than one Q-binding site [11, 13, 14], and the data have been interpreted in terms of two sites (Q L or Q H ) with the inhibitors binding to one or the other Q-binding sites. The reactivity of the enzyme with synthetic quinone analogues has also been examined, showing the roles of the ring substituents and the hydrophobic side chain in determining the kinetic parameters [15, 16]. …”
Section: Introductionmentioning
confidence: 99%